2020
DOI: 10.1021/acs.jpcc.0c07616
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Intramolecular Charge Transfers in Multimodular Donor–Acceptor Chromophores with Large Two-Photon Absorption

Abstract: New multimodular donor–acceptor chromophores combining phenothiazine (D′), benzothiadiazole (A), and diphenylamine/carbazole (D) units in complex configurations (D−π–A−π–D′−π–A−π–D and D–A−π–D′−π–A–D) were designed, synthesized, and investigated for their peculiar intramolecular charge transfer (ICT) behavior. In these organic materials, the modification of the end–capping donor units and the extension of π-conjugation are key factors in tuning their optical, photophysical and electrochemical properties, as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…Furthermore, as a result of reduced symmetry, both HOMO → LUMO and HOMO–1 → LUMO configurations contribute to S 1 and S 2 states, indicating a stronger hybridization of LE and CT characters. We note that excited-state symmetry breaking has been reported previously for some molecules exhibiting similar π-architectures to 2 EHO-TPA-CNPE and 2EHO-TPA-PE . Moreover, it has been shown that excited-state symmetry breaking is mainly driven by solvent fluctuations in polar environments, which is also accompanied by increasing CT character, whereas in weakly polar media, solvent fluctuations cannot induce such an effect and the excited state remains mainly delocalized over the entire π-backbone . This interaction picture is quite comparable to what was observed in the Lippert–Mataga curves (Figure ) along with the excited state analysis in different geometries (Figure ) for 2 EHO-TPA-CNPE and 2EHO-TPA-PE molecules.…”
Section: Results and Discussionsupporting
confidence: 86%
“…Furthermore, as a result of reduced symmetry, both HOMO → LUMO and HOMO–1 → LUMO configurations contribute to S 1 and S 2 states, indicating a stronger hybridization of LE and CT characters. We note that excited-state symmetry breaking has been reported previously for some molecules exhibiting similar π-architectures to 2 EHO-TPA-CNPE and 2EHO-TPA-PE . Moreover, it has been shown that excited-state symmetry breaking is mainly driven by solvent fluctuations in polar environments, which is also accompanied by increasing CT character, whereas in weakly polar media, solvent fluctuations cannot induce such an effect and the excited state remains mainly delocalized over the entire π-backbone . This interaction picture is quite comparable to what was observed in the Lippert–Mataga curves (Figure ) along with the excited state analysis in different geometries (Figure ) for 2 EHO-TPA-CNPE and 2EHO-TPA-PE molecules.…”
Section: Results and Discussionsupporting
confidence: 86%
“…The PTZ unit is an electron-rich tricyclic heteroarene with nonplanar butterfly structure, characterized by the presence of powerful electron-donor sulfur and nitrogen atoms . In the literature, the photophysical properties and the HOMO–LUMO energy levels of PTZ derivatives have been easily modulated by substitutions at the nitrogen and the 3,7-positions of the phenothiazine unit. , Our group has functionalized the 3,7-positions of the phenothiazine unit by using polycyclic aromatic hydrocarbons of increasing complexity or strong acceptors such as benzothiadiazole or tetracyanobutadiene. , In the literature, push–pull phenothiazine–naphthalimide systems have been successfully employed in some optoelectronic applications. However, the research on varying the oxidation state of the sulfur atom (sulfides, sulfoxides, and sulfones) in the thiazine ring of phenothiazine is still very limited. In this study, we have synthesized new naphthalimide and phenothiazine-based systems, in which we have changed the oxidation state of the sulfur atom on the thiazine ring to investigate its effect on the photonic properties of the obtained materials.…”
Section: Introductionmentioning
confidence: 99%
“…21 In the literature, the photophysical properties and the HOMO− LUMO energy levels of PTZ derivatives have been easily modulated by substitutions at the nitrogen and the 3,7positions of the phenothiazine unit. 22,23 Our group has functionalized the 3,7-positions of the phenothiazine unit by using polycyclic aromatic hydrocarbons of increasing complexity 24 or strong acceptors such as benzothiadiazole 25 or tetracyanobutadiene. 26,27 In the literature, push−pull phenothiazine−naphthalimide systems have been successfully employed in some optoelectronic applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Excited-state symmetry breaking (ES-SB) in multibranched electron donor–acceptor (D–A n or A–D n ) conjugates has focused considerable attention over the past few years. One major interest for these molecules stems from their large cross-section for two-photon absorption (TPA), , which makes them attractive for a broad variety of applications, ranging from fluorescence imaging to microfabrication. However, the strong solvent dependence of their excited-state properties makes them intriguing per se. Upon optical excitation in a nonpolar medium, their electronic structure is generally symmetric, while in polar environments, the symmetry of the electronic distribution breaks, resulting in the partial or complete localization of the excitation on one of the D–A branches.…”
mentioning
confidence: 99%